Anda di halaman 1dari 2

Kerjakan soal berikut dengan seksama!

Diketahui :
ΔH°f  CO2(g) = –394 kJ/mol; ΔH°f H2O(l) = –286 kJ/mol; ΔH°f  C2H4(g) = 52 kJ/mol; ΔH°f SO2(g) = –297 kJ/mol;
ΔH°f H2S(g) = 21 kJ/mol.
Hitung ΔH° untuk reaksi berikut.
(a) C2H4(g) + 3O2(g)→ 2CO2(g) +2H2O(l)
(b) SO2(g) + 2H2S(g)→ 2H2O(l) + 3S(s)

Kerjakan soal berikut dengan seksama!
Diketahui :
ΔH°f  CO2(g) = –394 kJ/mol; ΔH°f H2O(l) = –286 kJ/mol; ΔH°f  C2H4(g) = 52 kJ/mol; ΔH°f SO2(g) = –297 kJ/mol;
ΔH°f H2S(g) = 21 kJ/mol.
Hitung ΔH° untuk reaksi berikut.
(a) C2H4(g) + 3O2(g)→ 2CO2(g) +2H2O(l)
(b) SO2(g) + 2H2S(g)→ 2H2O(l) + 3S(s)

Kerjakan soal berikut dengan seksama!
Diketahui :
ΔH°f  CO2(g) = –394 kJ/mol; ΔH°f H2O(l) = –286 kJ/mol; ΔH°f  C2H4(g) = 52 kJ/mol; ΔH°f SO2(g) = –297 kJ/mol;
ΔH°f H2S(g) = 21 kJ/mol.
Hitung ΔH° untuk reaksi berikut.
(a) C2H4(g) + 3O2(g)→ 2CO2(g) +2H2O(l)
(b) SO2(g) + 2H2S(g)→ 2H2O(l) + 3S(s)

Kerjakan soal berikut dengan seksama!
Diketahui :
ΔH°f  CO2(g) = –394 kJ/mol; ΔH°f H2O(l) = –286 kJ/mol; ΔH°f  C2H4(g) = 52 kJ/mol; ΔH°f SO2(g) = –297 kJ/mol;
ΔH°f H2S(g) = 21 kJ/mol.
Hitung ΔH° untuk reaksi berikut.
(a) C2H4(g) + 3O2(g)→ 2CO2(g) +2H2O(l)
(b) SO2(g) + 2H2S(g)→ 2H2O(l) + 3S(s)

Kerjakan soal berikut dengan seksama!
Diketahui :
ΔH°f  CO2(g) = –394 kJ/mol; ΔH°f H2O(l) = –286 kJ/mol; ΔH°f  C2H4(g) = 52 kJ/mol; ΔH°f SO2(g) = –297 kJ/mol;
ΔH°f H2S(g) = 21 kJ/mol.
Hitung ΔH° untuk reaksi berikut.
(a) C2H4(g) + 3O2(g)→ 2CO2(g) +2H2O(l)
(b) SO2(g) + 2H2S(g)→ 2H2O(l) + 3S(s)

Kerjakan soal berikut dengan seksama!
Diketahui :
ΔH°f  CO2(g) = –394 kJ/mol; ΔH°f H2O(l) = –286 kJ/mol; ΔH°f  C2H4(g) = 52 kJ/mol; ΔH°f SO2(g) = –297 kJ/mol;
ΔH°f H2S(g) = 21 kJ/mol.
Hitung ΔH° untuk reaksi berikut.
(a) C2H4(g) + 3O2(g)→ 2CO2(g) +2H2O(l)
(b) SO2(g) + 2H2S(g)→ 2H2O(l) + 3S(s)
Kerjakan soal berikut dengan seksama!
Diketahui :
ΔH°f  CO2(g) = –394 kJ/mol; ΔH°f H2O(l) = –286 kJ/mol; ΔH°f  C2H4(g) = 52 kJ/mol; ΔH°f SO2(g) = –297 kJ/mol;
ΔH°f H2S(g) = 21 kJ/mol.
Hitung ΔH° untuk reaksi berikut.
(a) C2H4(g) + 3O2(g)→ 2CO2(g) +2H2O(l)
(b) SO2(g) + 2H2S(g)→ 2H2O(l) + 3S(s)